Image Based Plant Leaf Disease Recognition and Estimation System - Sheela , N; Harsha , BM; Shastri, Nikhil; Bhat, Gurudatt (International Journal of Computer Sciences and Engineering, 2019)
Agriculture is the back-bone of country`s economy, where farmer`s source of income widely depends upon farming. During the cultivation of crops, it is required to properly monitor and due to change in atmospheric condition or the loss of soil nutrition these crops get encountered with certain type of diseases. Health monitoring and disease detection on plants is very critical for sustainable agriculture. It is very difficult to monitor the plant diseases manually. It requires tremendous amount of work, expertise in the plant diseases, and also require the excessive processing time. Thus farmer cannot recognize easily because of which they incur loss in production and yield. So here we propose the system where we can detect the disease based on the leaf image and diagnose for proper medication based on the result.